2021
DOI: 10.1038/s41598-020-80858-1
|View full text |Cite
|
Sign up to set email alerts
|

Development of an immune-related gene pairs index for the prognosis analysis of metastatic melanoma

Abstract: Melanoma is a skin cancer with great metastatic potential, which is responsible for the major deaths in skin cancer. Although the prognosis of melanoma patients has been improved with the comprehensive treatment, for patients with metastasis, the complexity and heterogeneity of diffuse diseases make prognosis prediction and systematic treatment difficult and ineffective. Therefore, we established a novel personalized immune-related gene pairs index (IRGPI) to predict the prognosis of patients with metastatic m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…Immune-related gene pairs have been reported as emerging biomarkers to predict clinical outcomes 36, 37, 52 . Traditional methods select signatures from prognostic marker pairs, while TimiGP yields the enriched IMGPs that not only provide clinical insights but also reflect the functional cell interactions (Figure 4A), which is supposed to facilitate the model construction.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Immune-related gene pairs have been reported as emerging biomarkers to predict clinical outcomes 36, 37, 52 . Traditional methods select signatures from prognostic marker pairs, while TimiGP yields the enriched IMGPs that not only provide clinical insights but also reflect the functional cell interactions (Figure 4A), which is supposed to facilitate the model construction.…”
Section: Resultsmentioning
confidence: 99%
“…Despite this, it remains statistically and computationally challenging to identify the best combination of gene pair signatures due to the quadratically combinatorial complexity. While recent studies have revealed the advantage of immune-related gene pairs in developing prognostic signatures 36, 52 , the quadratic number of candidate genes still complicates the modeling process. Recent efforts focused on the improvement of machine-learning algorithms for variable selection and model fittings, which remain of poor quality in oncology 77 .…”
Section: Discussionmentioning
confidence: 99%
“…Multiple prognostic hub genes still cannot easily prompt the prognosis and risk of ESCC patients. To solve this problem, a prognostic risk model was established using the immune-related gene prognostic index, which could effectively predict the prognostic risk and immune response of ESCC patients ( Huang et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Considering the cancer is closely related to immune, clinical treatment of tumor immune microenvironment [42][43][44][45]. IRGPI must be considered and immune cell infiltration between the relevant assessment can be used to reflect the state of microenvironment [46][47]. Here, we show that IRGPI and Plasma cells, Monocytes, Macrophages The infiltration level of M0 was significantly correlated (P <0.05), and it was mainly enriched in immune-related functions such as pDCs,Type II IFN, REponse and TIL.…”
Section: Discussionmentioning
confidence: 99%